Risk assessment and management of preoperative venous thromboembolism following femoral neck fracture - Ze-Nan Xia; Ke Xiao; Wei Zhu; Bin Feng; Bao-Zhong Zhang; Jin Lin; Wen-Wei Qian; Jin Jin; Na Gao; Gui-Xing Qiu; Xi-Sheng Weng (Journal of Orthopaedic Surgery and Research, 2018)
Abstract Background Limited studies are available to investigate the prevalence of preoperative venous thromboembolism (VTE) in elderly patients with femoral neck fractures. Our primary aim was to determine the incidences of VTE and its risk or protective factors in such patient population. The secondary objective was to evaluate the need of therapeutic anticoagulation for isolated calf muscular venous thrombosis (ICMVT) prior to femoral neck fracture surgery. Methods This is a retrospective case-control study, including 301 femoral neck fracture patients who were admitted to our institution between January 2014 and March 2017. Bilateral Doppler ultrasonography was performed in each of the patients as a preoperative VTE screening. The event rate of VTE was calculated, and significant risk or protective factors were determined by using a multivariate logistic regression model. Patients with ICMVT were divided into anticoagulation and no anticoagulation groups to assess the efficacy and safety of preoperative therapeutic anticoagulation. Intraoperative blood loss, drainage volume, blood transfusion, perioperative hemoglobin change, and rate of thrombosis extension were compared between the two groups. Results The overall preoperative incidence of VTE in patients with femoral neck fracture was 18.9% (57/301), in which deep vein thrombosis (DVT) was 18.9% and pulmonary embolism (PE) was 1%. Among the DVT cases, 77.2% (44/57) were ICMVTs. Multiple fractures (odds ratio [OR] = 9.418; 95% confidence interval [CI] = 2.537 to 34.96), coexisting movement disorder (OR = 3.862; 95% CI = 1.658 to 8.993), bed rest for more than 7 days (OR = 2.082; 95% CI = 1.011 to 4.284) as well as elevated levels of D-dimer (OR = 1.019; 95% CI = 1.002 to 1.037) and fibrinogen (OR = 1.345; 95% CI = 1.008 to 1.796) led to an increase in the risk of VTE, while the recent use of antiplatelet drug (OR = 0.424; 95% CI = 0.181 to 0.995) and prophylactic anticoagulation (OR = 0.503; 95% CI = 0.263 to 0.959) decreased the risk of VTE. For the 39 patients with ICMVT undergoing femoral neck fracture surgery, there were no significant differences in the rate of thrombosis extension between anticoagulation and no anticoagulation groups, but significantly decreased postoperative hemoglobin was observed in the anticoagulation group. Conclusion Our findings showed a high prevalence of preoperative VTE in elderly patients with femoral neck fracture, with risk factors identified. We found that the most detected VTE were ICMVTs. Our study suggested that a direct surgery without preoperative use of therapeutic anticoagulation for ICMVT would not reduce the risk of thrombus extension, and the therapeutic use of anticoagulation may worsen postoperative anemia.